New developments in neonatal respiratory management - I-Ling Chen; Hsiu-Lin Chen (Pediatrics and Neonatology)
Respiratory distress syndrome (RDS) is the major cause of respiratory failure in preterm infants due to immature lung development and surfactant deficiency. Although the concepts and methods of managing respiratory problems in neonates have changed continuously, determining appropriate respiratory treatment with minimal ventilation-induced lung injury and complications is crucially important. This review summarizes neonatal respiratory therapy's advances and available strategies (i.e., exogenous surfactant therapy, noninvasive ventilation, and different ventilation modes), focusing on RDS management.